Phytochemical Constituents of Propolis Flavonoid, Immunological Enhancement, and Anti-porcine Parvovirus Activities Isolated From Propolis - Ma, Xia; Guo, ZhenHuan; Li, Yana; Yang, Kun; Li, Xianghui; Liu, Yonglu; Shen, Zhiqiang; Zhao, Li; Zhang, Zhiqiang (Frontiers in Veterinary Science, 2022)
Propolis was widely used in health preservation and disease healing, it contains many ingredients. The previous study had been revealed that the ethanolic or water extracts of propolis has a wide range of efficacy, such as antiviral, immune enhancement, anti-inflammatory and so on, but its antiviral components and underlying mechanism of action remain unknown.In this study, we investigated the chemical composition, and anti-PPV and immunological enhancement of Propolis flavone ethanolic of extracts propolis.Chemical composition of Propolis flavone was distinguished by UPLC-Q/TOF-MS/MS analysis.In this study, the presence and characterized of 26 major components was distinguished in negative ionization modes.To evaluate the effects of propolis flavonoid used as adjuvant on the immune response of Landrace-Yorkshire hybrid sows immunized with an inactivated vaccine of porcine parvovirus (PPV). Fourty Landrace-Yorkshire hybrid sows were randomly assigned to one of 4 groups, and the sows in three adjuvant groups were intramuscular injected PPV vaccine with 2.0 mL propolis flavonoid adjuvant (PA), Aluminum salt adjuvant (AA) or oilemulsion adjuvant (OA), respectively. After that, serum hemagglutination inhibition antibody titers, specific IgM and IgG subclasses were measured to evaluate the adjuvant effects of propolis flavonoid on the humoral immune responses, as well as peripheral lymphocyte proliferation activity, and serum concentrations of Th1 and Th2 cytokines for cellular immunity. Results indicated an enhancing effect of PA on IgM, IL-2, IL-4, IFN-γ and the IgG subclass responses. Especially in the effect of improving cellular immune response, the PA was the best. These findings suggested that PA can significantly enhance the immune responses against PPV vaccine and could be an alternative way to improve PPV vaccination in sows.Furthermore, we screened the PF chemical components the effective of anti-PPV. Ferulic acid have a excellently anti-PPV effective.